Evaluating the Efficacy and Stability of Expired Ciprofloxacin: A Comprehensive Assessment (Al-Farooq Journal of Sciences, 2026)
Medications that have exceeded their shelf life may degrade, become ineffective, or potentially harmful. Drug manufacturers and certain health organizations generally recommend discarding medications once the expiration date on the packaging has passed. However, it is important to note that the expiration date does not always definitively indicate that a drug has spoiled. The expiration date of antibiotics is significant as by this date the customer ensures the drug is effective, stable and safe. After this date, the active ingredient may destroy, leading to reduction in effectiveness and failure to treat infections, which can be reason for antibiotic resistance. This study aims to compare the antimicrobial activity of expired ciprofloxacin as example for antibiotics against standard bacterial strains with that of non-expired ciprofloxacin, Findings from this study could inform guidelines on the safe use of expired antibiotics. The study used several bacterial strains (Staphylococcus aureus, Escherichia coli, Salmonella and Shigella Flexenari ) and the consistency in results across all strains supports the conclusion that expired Ciprofloxacin may still be effective. The study did not evaluate the long-term degradation kinetics of Ciprofloxacin only a single time point (expired and  non-expired) was compared. In addition, a larger sample size and multiple batches of expired Ciprofloxacin would improve reliability. Further laboratory research was needed to evaluate the effectiveness of expired antibiotics, especially in countries facing medication shortages or during emergencies and patients should avoid using expired antibiotics without professional consultation, even if they appear to be effective, to reduce the risk of reduced potency or bacterial resistance. In addition, Provide clear regulatory guidance from health authorities (e.g., Ministries of Health or Food and Drug Administrations) on the safe use of certain expired medications when necessary.
Keywords: Ciprofloxacin, Antibiotics, Drug Efficacy, Drug Stability, Pharmaceutical Quality